PEGylation of PLGA and PCL nanoparticles enhanced the cytotoxicity of loaded 5-flurouracil - Ashour, Abdelkader Elbadawy Abbas; Badran, Mohammad; Kumar, Ashok; Hussain, Tajamul; Alsarra, Ibrahim; Yassin, Alaa Eldeen (2017)
Introduction: The high metabolic rate and the short biological half-life of 5-flourouracil (5-FU) required a continuous administration of large doses and consequently resulting in high profile of adverse effects. Incorporation of 5-FU into biodegradable nanoparticles (NPs) would enhance the therapeutic efficacy through prolongation of the biological half-life and the duration of tumour exposure to 5-FU. This study aimed to monitor the effect of physical incorporation of PEG on the attributes of 5-FU-loaded polymeric NPs.